2017
DOI: 10.17581/bp.2017.06105
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of in vitro and ex vitro regeneration and micromorphological studies of Micrococca mercurialis (L.) Benth.

Abstract: A regeneration protocol has been successfully developed using nodal segments and leaf explants of Micrococca mercurialis (L.) Benth. The surface sterilized leaf explants were induced to proliferative green colored callus on Murashige and Skoog (MS) me dium supplemented with 0.5 mg l -1 of 2,4-dichlorophenoxyacetic acid (2,4-D). Shoots were regenerated from the callus on MS medium sup plemen ted with 0.5 mg l -1 6-benzylaminopurine (BAP). The nodal shoot segments res ponded on MS medium augmented with 1.0 mg l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Nine shoots were produced by Lavia et al (1994) from the callus cultures of T. ulmifolia on MS medium fortified with NAA and BAP. The efficacy of BAP over other cytokinins for the establishment of cultures and multiplication of shoots has been reported by several authors for many plant species (Rathore et al, 2013;Cheruvathur et al, 2015;Lodha et al, 2015;Manokari and Shekhawat, 2017b). Zhang et al (2010) reported BAP as a better cytokinin for bud breaking and reinvigoration in Pinus radiata shoot cultures.…”
Section: Shoot Multiplication and Maintenance Of The Culturesmentioning
confidence: 83%
“…Nine shoots were produced by Lavia et al (1994) from the callus cultures of T. ulmifolia on MS medium fortified with NAA and BAP. The efficacy of BAP over other cytokinins for the establishment of cultures and multiplication of shoots has been reported by several authors for many plant species (Rathore et al, 2013;Cheruvathur et al, 2015;Lodha et al, 2015;Manokari and Shekhawat, 2017b). Zhang et al (2010) reported BAP as a better cytokinin for bud breaking and reinvigoration in Pinus radiata shoot cultures.…”
Section: Shoot Multiplication and Maintenance Of The Culturesmentioning
confidence: 83%
“…When producing Persian walnut in vitro explants, it is crucial to undergo hardening and acclimatization processes. This is due to the dysfunctional stomata of walnut in vitro-plantlets, resulting in excessive transpiration and heightened sensitivity to environments with increased evaporative demands and solar radiation (Chandra et al, 2010;Rathore et al, 2013;Manokari and Shekhawat, 2017). Plants are heterotrophic or mixotrophic under in vitro conditions, and their photosynthetic activity is limited (the carbon source is provided in the form of sugar).…”
Section: Discussionmentioning
confidence: 99%
“…ZnO-NPs can be synthesized in different crystal phases but the most stable one is hexagonal wurtzite structure [15]. Over the years, several methods for synthesizing ZnO-NPs including chemical reduction [16], thermal decomposition [17], photochemical reduction [18], electrochemical [19], hydrothermal [20], laser irradiation [21], pyrolysis [22], etc. have been applied, but limitations like toxicity of chemicals and harsh synthetic conditions are associated with these methods [23].…”
Section: Introductionmentioning
confidence: 99%